Collodion Baby And Cholestasis: A Rare Case Report - Bagus Setyoboedi; Rendi Aji Prihaningtyas; Syania Mega Octariyandra (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Collodion baby with cholestasis is an uncommon condition. The term